Mai langka'wei / Nurul Izzati Saperi - Saperi, Nurul Izzati (Universiti Teknologi MARA, Kedah, 2025)
The Mai Langka'Wei travel book. which highlights the rich cultural legacy and stunning sights of Langkawi Island, is an innovative and eye-catching product made to commemorate the Experience Kedah 2025 campaign. This book, which is intended for readers between the ages of 10 and 25, combines lively doodle images with interesting text that informs. amuses, and piques readers' interest in Longkowi's distinctive attractions. Fundamentally, the book is an imaginative examination of the island"s fabled legends. famous sites, and deleclable regional food, which makes it an engaging travel guide and on invaluable tool for everyone cl.Kious about this well-known location. Through vibrant visuals and in-depth narrative. the Langkawi legends such as the sorrowful yet engrossing story of Mahsuri's Tomb come to life. In addition to other intriguing legends that ore ingrained in Langkawi culture, readers ore inlroduced to Gunung Raya, which is thought to be a giant that has transformed into a mountain. In addition to captivating the mind, these tales help people understand the island's historical and cultural significance on a deeper level. In addition, the book provides a thorough overview of Langkawi's top attractions in on interesting and eye-catching manner. Famous locations like the beautiful Chenang Beach, a haven for leisure and waler sports. and the Longkowi Cable Car, which provides breathtaking panoramic views of the i~and, are highfighted extensively. Additionally, the book highlights lesser-known jewels, inspiring readers to find hidden gems and unusual encounters all across the island. The book makes sure readers hove a comprehensive grasp of the island's amenities, whether they ore visiting his1oricol monuments or strolling through the verdant woods of Langkawi. The gastronomic pleasures of Langkowi are a major part of its allure. and Mai Langka'Wei gives the island respect by including sections devoted ta its well-known regional cuisine. With vivid images that bring the cuisine to life, the book highlights Langkawi's gastronomic diversity, from the mouthwatering tastes of laksa ta the finest seafood served with local flare. These sections provide readers insights on the cultural importance of the cuisine in addition to tempting them to eat the dishes. The use of vibrant doodle-style illustrations is what distinguishes Mai Langka'Wei and makes the book incredibly captivating and approachable for its intended readership. In addition to improving the narrative. the drowings offer visual signals that make the information simple lo comprehend and enjoyable lo explore. Younger readers are drawn lo the book's creative style. which makes ii the ideal combination of enjoyment and information. Its lightweight form makes it the pertecl travel companion, and its attractive appearance guarantees thal ii will also serve as a memento for anyone who want lo treasure their time spent in Longkowi. In the end, Mai Longka'Wei is a celebration of Langkawi's culture. history, and beauty rather than merely a tourism guide. The book is a must-have for everyone interested in visiting or learning more about this fascinating island since it effectively promotes Langkawi tourism and leaves a lasting impact on readers by fusing educational material with imaginative illustrations.